Lost in Translation: Qualitative Data Collecting and Translating Challenges in Multilingual Settings in Information Systems Research - Demeke, Wegene; Ryan, Bruce (University of Dar es Salaam Library Journal, 2022)
In this paper under-researched methodological issues in information systems research of multilingual interview data collection and translation using translators explored. Observations field notes were collected during the study of the role of ICT for poverty reduction using Participatory Budgeting (PB) in Brazil. A systematic literature search conducted to find the methods used for collecting qualitative data in information systems research from 2010 to 2021. The identified research gap in data collecting and translating presented. Reflexive method used to analyse the researchers ' observations field notes. The findings of the research recommended data collecting and data translation framework: single back-translation for data validity and accuracy. The work also presented the key elements of qualitative data collection, timing, follow-up questions, and interpretation. We recommend researchers to make available the data collecting instruments and collected data in the original and target languages to provide transparency, data validity, and provides data access for future research.